2015
DOI: 10.1021/acs.jpcc.5b07841
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Precise Redox Properties of Oxygen-Doped Single-Walled Carbon Nanotubes Based on in Situ Photoluminescence Electrochemistry

Abstract: Single-walled carbon nanotubes doped with a limited amount of oxygen (O-doped SWNTs) are expected to be novel materials due to the appearance of red-shifted new emission and enhancement of the luminescence quantum yields compared to those of pristine SWNTs, which are of importance for the development of high performance biosensors, imaging materials, and optical devices. The appearance of the new optical properties is due to the change in the electronic states induced by the oxygen doping (Odoping) of the SWNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 44 publications
2
31
1
Order By: Relevance
“…E 11 * PL at wavelengths above 1000 nm is promising for the development of high‐resolution and high‐depth imaging techniques in biomedical applications and secure telecommunication devices . Defect doping has been achieved through oxygen‐doping using ozonization treatment,, and also through sp 3 defect doping using aryl modification (diazonium chemistry) and reductive alkylation . The key is achieving a small amount of chemical modification (local functionalization) that produces doped sites on the SWNTs , .…”
Section: Figuresupporting
confidence: 70%
“…E 11 * PL at wavelengths above 1000 nm is promising for the development of high‐resolution and high‐depth imaging techniques in biomedical applications and secure telecommunication devices . Defect doping has been achieved through oxygen‐doping using ozonization treatment,, and also through sp 3 defect doping using aryl modification (diazonium chemistry) and reductive alkylation . The key is achieving a small amount of chemical modification (local functionalization) that produces doped sites on the SWNTs , .…”
Section: Figuresupporting
confidence: 70%
“…GOx activation with glucose may allow bound GOx to behave as an electron donor to oxygen‐induced p‐doped sites. Previous studies have shown that these p‐doped sites behave as exciton trap sites that decrease SWCNT fluorescence . The addition of reducing agents, such as dithiothreitol (DTT), Trolox, and β‐mercaptoethanol have been shown to reduce p‐doped defect sites, and this reduction leads to SWCNT brightening .…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the observed HOMO and LUMO level shifts depended on the O-doped structures21. In the sp 3 defect doping system, substituents on the introduced aryl groups provided a band gap variation14.…”
mentioning
confidence: 98%